Influence of Immediate Dentin Sealing on the Shear Bond Strength of Pressed Ceramic Luted to Dentin with Self-Etch Resin Cement - Robert Dalby; Ayman Ellakwa; Brian Millar; F. Elizabeth Martin (International Journal of Dentistry)
Objectives. To examine the effect of immediate dentin sealing (IDS), with dentin bonding agents (DBAs) applied to freshly cut dentin, on the shear bond strength of etched pressed ceramic luted to dentin with RelyX Unicem (RXU) cement. Method. Eighty extracted noncarious third molars were ground flat to expose the occlusal dentin surfaces. The teeth were randomly allocated to five groups (A to E) of sixteen teeth each. Groups A to D were allocated a dentin bonding agent (Optibond FL, One Coat Bond, Single Bond, or Go!) that was applied to the dentin surface to mimic the clinical procedure of IDS. These specimen groups then had etched glass ceramic discs (Authentic) luted to the sealed dentin surface using RXU. Group E (control) had etched glass ceramic discs luted to the dentin surface (without a dentin bonding agent) using RXU following the manufacturer’s instructions. All specimens were stored for one week in distilled water at room temperature and then shear stressed at a constant cross-head speed of 1 mm per minute until failure. Statistical analysis was performed by ANOVA followed by post hoc Tukey HSD method (𝑃<0.05) applied for multiple paired comparisons. Results. The shear bond strength results for group A to E ranged from 6.94±1.53 to 10.03±3.50 MPa. One-way ANOVA demonstrated a difference (𝑃<0.05) between the groups tested and the Tukey HSD demonstrated a significant (𝑃<0.05) difference between the shear bond strength (SBS) of Optibond FL (Group A) and Go! (Group D). There was no statistical difference (𝑃>0.05) in the SBS between the test groups (A–D) or the control (group E). Conclusion. IDS using the dentin bonding agents tested does not statistically (𝑃>0.05) affect the shear bond strength of etched pressed ceramic luted to dentin with RXU when compared to the control.